Concurrent and prospective relations between aberrant stress-induced frontal alpha asymmetry and cannabis use disorder - Brandon S. Schermitzler; Julia Y. Gorday; Michael Griffin; Richard J. Macatee (Addiction Neuroscience)
Background: Cannabis Use Disorder (CUD) is prevalent and associated with significant disability. Stress potentiation of drug use motivation is a mechanism implicated in CUD; however, little is known about the neurobiological mechanisms through which stress impacts cannabis use motivation. Frontal alpha asymmetry (FAA), an index of approach motivation, is sensitive to acute stress, so this study sought to examine the relationship between stress-potentiated FAA and cannabis-related problems. Method: Non-treatment-seeking regular cannabis users in a stress task study (N = 102) and a control task study (N = 52) completed a resting state task with concurrent electroencephalogram recording before and after a stressor or control task. Changes in FAA from pre- to post-task represented a neurophysiological index of approach motivation change. Participants completed self-report and clinician-assessed measures of cannabis-related problems. Participants in the stress study re-completed all study components three months later. Results: Relative to the control study, participants in the stress study showed a greater shift from right to left alpha-band power at frontal sites. More cannabis-related problems, but not past-month cannabis use sessions, correlated with a blunted stress-induced FAA response, which predicted greater maintenance of cannabis-related problems three months later. Baseline cannabis-related problems were not associated with changes in the stress-induced FAA response from baseline to follow-up, and changes in cannabis-related problems across the three-month study period were not associated with changes in the stress-induced FAA response. The stress-induced FAA response demonstrated good stability over three months. Conclusion: The stress-induced FAA response may represent a stable predictor of cannabis-related problems and may have implications for clinical practice.